A strategy for an initial assessment of the ecotoxicological effects of transformation products of pesticides in aquatic systems following a tiered approach. (April 2020) - Hensen, Birte; Olsson, Oliver; Kümmerer, Klaus
Highlights: A tiered approach was applied for the assessment of 45 known pesticide TPs. The consideration of TPs increase the number of substances that could pose a risk. The approach allowed for an initial toxicity screening of 94% of TPs assessed. 9 TPs showed strong and 20 TPs showed slight indication to be ecotoxic. Abstract: In order to conduct a fast and comprehensive toxicity screening of pesticide transformation products (TPs), this study used a tiered approach by a combination of in silico and experimental methods to determine the probability to be of relevance for risk assessment. The six pesticides Boscalid, Penconazole, Diuron, Terbutryn, Octhilinone (OIT), and Mecoprop were used as model compounds. Identification of corresponding environmental known and unknown TPs were done by literature analysis and photolysis experiments in combination. Aquatic solutions of the pesticides were photolysed to generate TPs which can be expected in the aquatic environment. The resulting mixtures were screened for TPs by high resolution LC-MS/MS. The herein developed approach was conducted at three different tiers: Literature review and in silico methods were used to predict exemplary the environmental bacterial toxicity and the genotoxicity of every single TP at tier I. In case of indications to be toxic, experiments at tier II were applied. Hereby, the photolytic mixtures containing parent compound and TPs were used for the consecutive toxicity test. Microtox assay for the parent compounds and the photolytic mixture was conducted to determine the acute and chronic toxicity and the growth inhibition of V. fischeri . Umu-tests were conducted to determine primary DNA damage. At tier III, single substance standards were used to conduct toxicity tests in case of toxic indication by previous tiers and availability of analytical standard. Identification of TPs revealed 45 known environmental TPs that originated from the six pesticides. The number of substances that need to be assessed was therefore more than sevenfold. By the tiered approach, it was possible to assess toxicological effects on environmental bacteria of 94% of the selected TPs. For 20% we found strong evidence to be toxic to environmental bacteria, as they were assessed at least at two tiers. For further 44% of the TPs we found slight evidence, as they could be assessed at one tier. Contrary, this approach turned out to be unsuitable to assess genotoxic effects of TPs neither by in silico tools nor by experiments. The number of substances that could probably pose a risk onto environment was quadrupled in comparison to the consideration of solely the parent compounds. Thus, this study demonstrates that the conducted screening approach allows for easy and fast identification of environmental relevant TPs. However, the study presented was a very first screening. Its applicability domain needs to be assessed further. For this purpose as a very next step the approach suggested here should be verified by applying additional endpoints and including additional parent compounds.